Compensating Farm Workers through Piece Rates: Implications on Harvest Costs and Worker Earnings: FE792/FE792, 2/2009 - Roka, Fritz M. (EDIS, 2009)
FE792, a 4-page fact sheet by Fritz M. Roka, explains how a piece rate payment system works and its implications on production costs and farm worker earnings. Includes references. Published by the UF Department of Food and Resource Economics, February 2009.